O livro jogador No1: a narrativa ficcional sob tensionamentos transmidiáticos - OLIVEIRA, Washington Freitas de (2021)
This research is a case study of the book Ready Player One by the American writer Ernest Cline from a perspective of transmedia narrative crossing. The choice of the book is due to the fact that it presents conditions for the reproduction of the transmedia phenomenon due to the existence in its narrative of 380 references to movies, games, music, etc. The work also stands out as one of the most read (Best seller) in 2011 in the US. In addition to the book, 13 more (observable) media are analyzed as required by transmedia studies. These media were selected from 380 references. To arrive at the quantity of thirteen references, two criteria were used: cited and described references contained in the challenges of keys and gates and the potential for piercing as a starting point. Our main objective is to investigate the use of multiple references (films, games, music, etc.) disposed in the construction of the narrative of the empirical object mentioned. The research problem that guided our study was: how do a set of references in the book Ready Player One give rise to a transmedia experience? With this problem as an axis, we turn to the analysis of the book’s narrative from a transmedia perspective of production. Transmedia descriptive and interpretive descriptive analysis were used as the method of data analysis (JENKINS, 2009b; LOPES, 2014). The analysis resulted in the description of how the transmedia perspective was manifested in the book and, finally, in the identification of production strategies(JENKINS, 2009a; SCOLARI, 2013; GOSCIOLA, 2014) that dialogued with the structure and content of the work.